2010
DOI: 10.17221/3016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen level and abomasal ulcerations in experimental abomasal displacement in sheep

Abstract: It is believed that serum pepsinogen levels could be useful for diagnosis of abomasal changes in cattle. Diagnosis of abomasal displacement (AD) is made via invasive and non-invasive techniques. None of the extant methods is a reliable indication of mucosal change. The applicability of serum pepsinogen levels for the diagnosis of changes in the mucous membrane of the abomasum in experimentally induced left and right AD in sheep was investigated in fourteen rams. Abomasal fluid samples were taken and the pH was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…Foreign bodies in the rumen [23] might be due to the development of pica, which is associated with nutritional deficiency and poor management practices [24,25]. The histopathological lesions observed in different organs of the goats in this study suggest degenerative and inflammatory responses and are in general agreement with those reported by Tariq et al [25] and Hajimohammadi et al [26].…”
Section: Discussionsupporting
confidence: 90%
“…Foreign bodies in the rumen [23] might be due to the development of pica, which is associated with nutritional deficiency and poor management practices [24,25]. The histopathological lesions observed in different organs of the goats in this study suggest degenerative and inflammatory responses and are in general agreement with those reported by Tariq et al [25] and Hajimohammadi et al [26].…”
Section: Discussionsupporting
confidence: 90%
“…These reports also support our results (Figure 2). Abomasal damage was not confirmed with necropsy in the present study but based on the previous studies in cattle (Hajimohammadi et al, 2010;Voros et al, 1984; Zadnik and Mesaric, 1999), the increase in plasma pepsinogen concentrations detected in this study may indicate the occurrence of abomasal damages in calves.…”
Section: Discussioncontrasting
confidence: 71%
“…High plasma pepsinogen concentrations are thought to be associated with vascular permeability in the abomasum, such as the melena group in this study, and any damage to the gastric mucosa allows the diffusion of hydrogen ions from the lumen to the mucosal tissues similarly to previous studies. The studies report that the diffusion of pepsin and pepsinogen to the mucosa causes injury to the gastric mucosa (Hajimohammadi et al, 2010;Voros et al, 1984;Zadnik and Mesaric, 1999). These reports also support our results (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cows with abomasitis, LDA, RDA and abomasal ulcers have increased serum pepsinogen levels (Mesarič et al, 2002). Hajimohammadi et al (2010) confirmed that serum pepsinogen levels were significantly higher in LDA and RDA affected sheep (investigated as a model for cattle). In contrast, Ohwada et al (2002) proved that serum pepsinogen concentrations in LDA, RDA and AV cows were significantly decreased compared with healthy cows.…”
Section: Discussionsupporting
confidence: 68%